Pengembangan E-LKPD Berbasis Kearifan Lokal Motif Batik Kota Serang dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Desi Pristiwanti; Aan Hendrayana; Lukman Nulhakin (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is motivated by the lack of development of teaching media that refers to regional culture, the learning activities and media used have not been able to foster students' motivation to hone critical thinking skills. This study intends to produce LKPD based on local cultural wisdom values of Serang city batik motifs in improving critical thinking skills.this from of research used the R&D (Research and Development) method with the ADDIE (Analyzer, design, Development, Implementation, Evaluation) model development design. Samples were taken using random sampling techniques to collect 33 samples. The research design used one group pretest and posttest. Data collection techniques were carried out by giving critical thinking ability tests, conducting teacher interviews, and student response questionnaires. Student' critical thinking abilities have increased with an N-Gain value of 0,56 which is included in the medium category. The conclusion is that the E-LKPD liveworksheet based on local wisdom can be used as an alternative learning media including an effort to improve students' critical thinking skills on the richness of Indonesian culture material.